2015
DOI: 10.4103/0971-9784.159804
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term survival after transcatheter aortic valve implantation: Results with respect to the anesthetic management and to the access route (transfemoral versus transapical)

Abstract: Context:Several studies have analyzed the long-term survival after transcatheter aortic valve implantation (TAVI). However, no previous studies have looked at survival beyond 1-year with respect to the type of anesthesia.Aims:The aim was to evaluate the mid-term survival after TAVI with respect to the type of anesthesia (general anesthesia [GA] vs. local anesthesia ± sedation [LASedation]) or the type of procedure (transfemoral [transfem] vs. transapical TAVI) performed.Settings and Design:Retrospective cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 23 publications
0
30
0
2
Order By: Relevance
“…43 44 Gauthier et al reported a lower risk of infectious complications for patients who received LAS for TAVI: they attributed this finding to the avoidance of bladder catheterisation, central venous catheter insertion and intubation. 28 Nevertheless, we could not identify a significant difference in the pneumonia rate between the LAS and GA groups, possibly because of the small number of studies that reported this outcome. Palermo et al described pneumonia rates of 0% for LAS versus 4.8% for GA; Covello et al reported rates of 0% for LAS versus 7% for GA; and Goren et al also found a lower incidence, with 2% for LAS versus 5% for GA.…”
Section: Length Of Staymentioning
confidence: 76%
See 1 more Smart Citation
“…43 44 Gauthier et al reported a lower risk of infectious complications for patients who received LAS for TAVI: they attributed this finding to the avoidance of bladder catheterisation, central venous catheter insertion and intubation. 28 Nevertheless, we could not identify a significant difference in the pneumonia rate between the LAS and GA groups, possibly because of the small number of studies that reported this outcome. Palermo et al described pneumonia rates of 0% for LAS versus 4.8% for GA; Covello et al reported rates of 0% for LAS versus 7% for GA; and Goren et al also found a lower incidence, with 2% for LAS versus 5% for GA.…”
Section: Length Of Staymentioning
confidence: 76%
“…We reviewed 35 full-text articles and identified 20 articles for inclusion in our review (figure 1). [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] All the studies were observational studies except one RCT. 32 Table 1 shows the baseline clinical characteristics of the included studies.…”
Section: Study Selection and Eligibility Criteriamentioning
confidence: 99%
“…The majority of participants included in our meta‐analysis were derived from 2 large prospective registries, with the lack of information regarding delirium diagnostic criteria and timing of the delirium screening . Interestingly, while these 2 large studies reported lower incidence of IHPOD after TAVR (e.g., 3.8% and 4.6%), small studies included in our analysis report higher incidence of IHPOD after TAVR . Several participant‐ and procedural‐related factors, including age at admission, comorbid condition, TAVR access, and hospital complication rate, could explain the differences in the incidence of IHPOD between these studies.…”
Section: Discussionmentioning
confidence: 89%
“…When inclusion and exclusion criteria were applied, 31 publications remained for assessment. 6,8,9,11,17, Most included studies were observational (14 prospective, 6,17,23,[26][27][28][29][30]33,35,37,41,44,47 6 propensity matched, 22,24,25,36,40,42 10 retrospective 8,9,11,31,32,34,38,43,45,46 ), with only one randomized controlled trial. 39 Differences in the differential diagnosis between POD and other comparable cognitive disorders, including dementia, depression, and schizophrenia, are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation